Rancang Bangun Smart Doorbell Menggunakan Sensor Ultrasonik HC-SR04 Berbasis IoT - Pratama, Ahmad Yudha; Perdana, Meilyana Winda; Jimmie, Jimmie (LPPM Institut Pendidikan Nusantara Global, 2025)
The development of Internet of Things (IoT)–based technology has opened significant opportunities for creating efficient and hygienic smart home devices. One such innovation is the Smart Doorbell, an automatic home doorbell system capable of detecting the presence of visitors without physical contact. This study is motivated by the limitations of conventional doorbells, which do not provide remote notifications and may potentially transmit diseases through direct touch. This research aims to design and build a Smart Doorbell system using an HC-SR04 ultrasonic sensor based on Arduino Uno to enhance user safety and convenience. The research methods include literature review, hardware and software design, and comprehensive system testing on the sensor, LCD, buzzer, and LED. The results show that the device successfully detects object distance accurately and displays visitor presence information through an LCD screen, accompanied by audio notifications via a buzzer. The system operates automatically without the need for physical interaction with a button, thereby improving efficiency and hygiene. In conclusion, this IoT-based Smart Doorbell is effective as a modern solution for home visitor notification systems. Future research is recommended to add a camera module and a DFPlayer Mini to provide more informative visual and audio notifications.